DETERMINATION OF THE OPTIMAL METHOD OF TREATMENT OF PATIENTS WITH ACUTE DESTRUCTIVE PANCREATITIS - B. N. Gurmikov; M. S. Bolokov; A. B. Apsheva (Кубанский научный медицинский вестник)
Currently, the question remains as to the appropriateness of percutaneous puncture-drainage, endoscopic and traditional surgery for acute destructive pancreatitis. The purpose of the work was to determine the management of patients, depending on ultrasonography and computed tomography of pathological changes of the pancreas The clinic treated 429 patients with acute pancreatitis. Of these destructive pancreatitis occurred in 96 (22,34 %) patients. 83 (86,46 %) patients underwent minimally invasive interventions (puncture and drainage under ultrasound navigation, laparoscopic drainage). The remaining 13 (13,54 %) patients underwent traditional intervention. The frequency of deaths was significantly lower in the group of patients with acute pancreatitis who underwent minimally invasive surgery. Selection surgical method in destructive pancreatitis should be determined on the basis of pathological changes to the pancreas and the surrounding tissue, detectable by ultrasound and computed tomography study. Optimal methods for the presence of liquid components are minimally invasive interventions under ultrasound navigation and laparoscopy.